2018
DOI: 10.1007/s00431-018-3113-2
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis calculator implementation reduces empiric antibiotics for suspected early-onset sepsis

Abstract: Pragmatic and feasible implementation of the sepsis calculator yields a 44% reduction of empirical use of antibiotics for EOS, without signs of delay or prolongation of treatment. These findings warrant a multicenter, nation-wide, randomized study evaluating systematic use of the sepsis calculator prediction model and its effects in clinical practice outside of the USA. What is known: • Significant overtreatment with antibiotics for suspected early-onset sepsis results in unnecessary costs, risks, and harms. •… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
81
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 14 publications
6
81
2
2
Order By: Relevance
“…There is a need for a simple and efficient predictor for identifying non‐infected neonates in the first few hours of life, so they can be protected from unnecessary antibiotic exposure and from the spread of multidrug‐resistant organisms. The EOS risk calculator has already been used in practice in some neonatal centres in Western countries and has been validated as a tool to reduce unnecessary antibiotic exposure in previous studies …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a need for a simple and efficient predictor for identifying non‐infected neonates in the first few hours of life, so they can be protected from unnecessary antibiotic exposure and from the spread of multidrug‐resistant organisms. The EOS risk calculator has already been used in practice in some neonatal centres in Western countries and has been validated as a tool to reduce unnecessary antibiotic exposure in previous studies …”
Section: Discussionmentioning
confidence: 99%
“…The EOS risk calculator has already been used in practice in some neonatal centres in Western countries and has been validated as a tool to reduce unnecessary antibiotic exposure in previous studies. [5][6][7] However, it is worth noting that there are limitations to applying the EOS risk calculator in China. First, it is still challenging for clinicians to recognise EOS early and begin treatment in symptomatic infected infants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the use of preventive antibiotic treatment in the neonate may affect normal microbial colonization (see Neuman, Forsythe, Uzan, Avni, & Koren, for a review). Although more prospective multicentered research is warranted before modifying care protocols, a recent study found that the use of antibiotics in neonates with suspected early‐onset sepsis can be reduced by 44% through a change in medical practices (Achten, Dorigo‐Zetsma, van der Linden, van Brakel, & Plötz, ).…”
Section: Influencing the Gut Microbiota In Early Developmentmentioning
confidence: 99%